2021
DOI: 10.1093/plcell/koab317
|View full text |Cite
|
Sign up to set email alerts
|

Fast and global reorganization of the chloroplast protein biogenesis network during heat acclimation

Abstract: Photosynthesis is a central determinant of plant biomass production, but its homeostasis is increasingly challenged by heat. Little is known about the sensitive regulatory principles involved in heat acclimation that underly the biogenesis and repair of chloroplast-encoded core subunits of photosynthetic complexes. Employing time-resolved ribosome and transcript profiling together with selective ribosome proteomics, we systematically deciphered these processes in chloroplasts of Chlamydomonas reinhardtii. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 74 publications
7
23
0
Order By: Relevance
“…In accordance with rising evidence for a linkage between the synthesis of chlorophyll and proteins in chloroplasts (Westrich et al, 2021; Trösch et al, 2022), we observed the accumulation of chlorophyll biosynthesis enzymes such as the magnesium protoporphyrin IX methyltransferase (CHLM) and protochlorophyllide reductase (POR) in D1 RNCs. A well-coordinated expression of chlorophyll-binding apoproteins and chlorophyll synthesis is required in the chloroplast to avoid the formation of harmful reactive oxygen species and phototoxic stress due to the accumulation of free, highly photoreactive chlorophyll molecules (Apel and Hirt, 2004; Wang and Grimm, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with rising evidence for a linkage between the synthesis of chlorophyll and proteins in chloroplasts (Westrich et al, 2021; Trösch et al, 2022), we observed the accumulation of chlorophyll biosynthesis enzymes such as the magnesium protoporphyrin IX methyltransferase (CHLM) and protochlorophyllide reductase (POR) in D1 RNCs. A well-coordinated expression of chlorophyll-binding apoproteins and chlorophyll synthesis is required in the chloroplast to avoid the formation of harmful reactive oxygen species and phototoxic stress due to the accumulation of free, highly photoreactive chlorophyll molecules (Apel and Hirt, 2004; Wang and Grimm, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Recent reports indicated that chloroplast ribosomes exhibit a large interaction network that connects the protein synthesis machinery with various metabolic pathways (Westrich et al, 2021; Trösch et al, 2022). Consistently, we identified among the 123 factors enriched in D1 RNCs 55 proteins that could be assigned to different metabolic pathways (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional redundancy and significant physical interactions between these proteins have been discovered previously. Using the yeast two hybrid system, bZIP16, bZIP68, and GBF1, were found to form heterodimers (Tano and Woodson, 2022;Trösch et al, 2022). Such heterodimerizations have also been observed between the GBF1, GBF2, and GBF3 proteins (Pesaresi et al, 2007;Toyokuni et al, 2022;Trösch et al, 2022).…”
Section: Nuclear Components Involved In the Regulation Of Chloroplast...mentioning
confidence: 95%
“…Using the yeast two hybrid system, bZIP16, bZIP68, and GBF1, were found to form heterodimers (Tano and Woodson, 2022;Trösch et al, 2022). Such heterodimerizations have also been observed between the GBF1, GBF2, and GBF3 proteins (Pesaresi et al, 2007;Toyokuni et al, 2022;Trösch et al, 2022). GBF1 was also found to interact with other proteins in a variety of ways, including acting antagonistically with HY5 for the expression of RBCS-1A, acting additively with HY5 to regulate the expression of LHCB1.3 (Pesaresi et al, 2007), and acting antagonistically with MYC2, a bHLH TF, in blue light signaling and regulation of hypocotyl elongation (Tyagi, 2001;Tyagi and Gaur, 2003;Pesaresi et al, 2007).…”
Section: Nuclear Components Involved In the Regulation Of Chloroplast...mentioning
confidence: 99%